Integration of a novel Vernier-DSPM generator in a grid connected hybrid renewable energy system with battery storage - Abderrahmane Redouane; Rachid Saou; Youcef Belkhier; Amrane Oukaour (Results in Engineering)
This research investigates a hybrid renewable energy system (HRESs) connected to the grid that uses three energy sources: solar energy, wind energy, and battery energy. Unlike conventional wind turbine systems, this paper uses a direct-drive high torque low speed generator called the Vernier Doubly Salient Permanent Magnet Generator (V-DSPMG). The generator shaft is directly connected to the turbine shaft without a gearbox, which enhances the performance of the wind power system. A mathematical model of the components of the grid-connected system is presented. An efficient Tip Speed Ratio (TSR) based sliding mode control (SMC) maximum power point tracking (MPPT) algorithm based on constant plus proportional rate reaching law is utilized to extract the optimal power from the wind turbine. A perturb and observe (P&O) MPPT algorithm is used in the photovoltaic system because of its high efficiency and ease of implementation. To control the bidirectional power flow in the battery storage system, a proportional-integral (PI) current control is employed. Furthermore, this paper proposes a new super-twisting sliding mode control (NSTSMC) method to regulate the DC-Link voltage. To demonstrate its performance, a comparison is made with Super-Twisting SMC (STSMC) and conventional PI control. A five-level Active Neutral Point Clamped (5L-ANPC) DC/AC converter is proposed for efficient power flow, better output voltage harmonic spectrum, and better power quality injected into the grid. The considered system is performed under MATLAB/Simulink and OPAL-RT real time validation. The results demonstrate that this configuration establishes a highly reliable and efficient energy system. Each energy source is skillfully engineered to autonomously meet power demands. If there is a shortfall in power from any single source, the system is designed to balance this using the other sources. This interconnected and supportive arrangement significantly amplifies the system's reliability and sustainability, making it an exemplary model in the realm of hybrid renewable energy systems for HRES.